The inflation-economic growth relationship in China - Ji, Xuechun (2009)
Abstract Both Inflation and economic growth are important variables in economy, and the relationship between them is quite complicated. Economists have tried different methods and used different samples trying to analyze the relationship between inflation and economic growth, however, there still exist not many consensus about the nature of inflation-growth relationship. China as one of the biggest developing countries in the world, has a special economic background. The economic transformation brings many problems, inflation has become the most one in recent years. In my dissertation, the analysis about the general correlation between inflation and economic growth will be done but will not be the main focus of my dissertation. I will analyze how the different sectors have influenced inflation-growth relationship, and the nature of the relationship, only in this way can I provide useful information and recommendations to solve the problems to policy makers. Secondary research and qualitative measure are conducted, so that qualitative analysis and comparisons will be made. The findings suggest that different markets will influence inflation-growth relationship in different ways, and the problems should also be solved in different ways by policy maker. Some positive inflation-growth correlation indicated by the data may not really be good for our long-term economic growth, so my dissertation provides a good example on how to analyze inflation-growth relationship in the future.